Clinical profile of patients with abdominal tuberculosis in rural North India - Agrahari, Saurabh; Utaal, Maneshwar Singh; Bali, Sharadendu (International Surgery Journal, 2019)
Background: Tuberculosis is a very serious health hazard in India. The nonspecific clinical features of abdominal tuberculosis (TB) have made its diagnosis difficult, which can lead to the poor outcome in patients who are not able to receive early treatment especially from rural areas. Aim of our study was to determine the clinical profile including various clinico-pathological manifestations, demographic profile, spectrum of clinical presentation, etiology, pathological and radiological investigations of patients with abdominal TB. Methods: A total of 30 patients with abdominal TB were analysed. All diagnosed patients received anti-tubercular treatment and were followed up at 1 to 3 months of ATT. Results: The disease was common in both sexes. Most common symptoms were abdominal pain (93%), weight loss (83%), anorexia (68%). Most commonly observed signs were ascities (73.3%) abdominal distension and abdominal tenderness (43.3%) and lymphadenopathy (40%). Most of the patient were diagnosed via radiological and histo-pathological studies. Evidence of active pulmonary TB was present in nearly three fourth of patients. CB-NAAT was positive in 73% of the patients. Most common site of involvement was ileocecal region (36.9%). All patients had a good clinical response to ATT. Conclusions: The diagnosis of GI tuberculosis is often delayed. The onset usually is insidious with symptoms present for many months before diagnosis. A considerable number of patients can be diagnosed from common but non-specific clinical features (like fever, weight loss, altered bowel habit, Abdominal pain and distension). Laparoscopic examination is the Gold standard for diagnosis of peritoneal tuberculosis. Although AFB detection is difficult, a representative tissue biopsy and radiological findings are good method of diagnosis of abdominal tuberculosis.